The mummy under the bed : essays on gender and methodology in the ancient Near East - Graef, Katrien de; Garcia-Ventura, Agnès; Goddeeris, Anne; Nakhai, Beth Alpert, 1951- (Zaphon, 2022)
"The present volume contains 17 contributions devoted to various methodological approaches to gender studies within the broad field of Ancient Near Eastern studies, including ancient history, archaeology, art history, Assyriology, Phoenician-Punic studies, and biblical studies. This collection is the result of presentations, exchanges, and discussions that took place during the third workshop on Gender, Methodology, and the Ancient Near East in Belgium from 8 to 10 April 2019. Over these three days, scholars from the four corners of the world descended on the Royal Academy of Dutch Language and Literature in the picturesque city of Ghent in order to exchange research findings, ideas, and hypotheses on gender-related topics within the realms of greater Mesopotamia, Egypt, and the Levant"-- Page 7.
Keywords: Gender identity -- Middle East -- Congresses.; Sex role -- Middle East -- Congresses.; Women -- Middle East -- Congresses.; Bronze age -- Middle East -- Congresses.; Mythology, Assyro-Babylonian -- Congresses.; Women -- Mythology -- Congresses.; Bible and feminism -- Congresses.; Femininity in the Bible -- Congresses.; Goddesses, Phoenician -- Congresses.; Mythology, Phoenician -- Congresses.; Mythologie assyro-babylonienne -- Congrès.; Femmes -- Mythologie -- Congrès.; Bible et féminisme -- Congrès.; Déesses phéniciennes -- Congrès.; Mythologie phénicienne -- Congrès.; HISTORY / Ancient / General; Bible and feminism; Bronze age; Femininity in the Bible; Gender identity; Goddesses, Phoenician; Mythology, Assyro-Babylonian; Mythology, Phoenician; Sex role; Women; Women -- Mythology; Middle East; Gender roles; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.